Aspects of time and narrative in the novels of J.M. Coetzee - Bruce, Alastair (Department of English Language and Literature, 2016)
Building on the approaches of critics such as David Attwell, and starting from the premise that the concepts of time and narrative are inextricably linked, this thesis aims to show how J.M. Coetzee's fictional narratives are concerned with the effects of historical time on both the characters of the novels and on the novels themselves; that is, more generally ,speaking, on literature. The study analyses the novels paying attention to their juxtaposition of literature and history and the tension between these two discourses. Coetzee tries to establish the legitimacy of a fictional, artistic time and space opposed to the violence of historical time and space. In so doing, he reveals the ironic dependence of literature on history as well as the metaphysical and ethical need for the continuing presence of literature in history. The novels are examined in sequence, allowing for illumination of trends and developments in Coetzee' s fiction. The first chapter shows how Dusklands is concerned with breaking down, mainly through parody, the oppressive structures that Coetzee finds in historical time. The second and third, on In the Heart of the Country and Waiting for the Barbarians respectively, discuss how the novels oppose history thematically and formatically. The chapters on Life and Times of Michael K and Foe show characters escaping the restrictive terms of history, and how the novels establish a "fictional realm". The Age of Iron chapter examines more closely the authority of this realm, and notes that the novel issues a plea for the continuation of fictional time and its potential for liberation. The previous five novels all express, ironically enough, reservations about the possible dependence of art or literature on history. The Master of Petersburg, so the chapter argues, takes the trend to its logical conclusion and offers a somewhat ironic look at the ethics of fiction writing.